(untitled) (Acta Scientiarum. Biological Sciences, 2018)
This study aimed to characterize the phytochemical compositions of three medicinal Brazilian plants’ leaves and bast extracts, and to determine their antibacterial activity on three foodborne and waterborne bacterial pathogens. Parkia platycephala, Pouteria ramiflora and Lophanthera lactescens leaves and basts were collected and aqueous and hydroalcoholic extracts were prepared. Qualitative screening of the phytochemical extracts was performed with three replicates and in triplicate in order to identify the bioactive compounds. The Minimal Inhibitory Concentration and Minimal Bactericide Concentration were determined by microdilution in broth and Escherichia coli, Salmonella typhimurium and Staphylococcus aureus growth was observed on agar plates. Phytochemical composition analysis allowed for the identification of anthraquinones, catechins, saponins, tannins, sesquiterpenlactones and other lactones in the three plants’ leaves and bast aqueous and hydroalcoholic extracts. Eighty-three percent of the plant extracts showed antibacterial activity against S. aureus, and P. platycephala extracts were the only ones that inhibited E. coli and S. typhimurium growth. The present study contributes significantly to the phytochemical composition characterization of three plant species commonly used in Brazilian traditional medicine. The plant extracts’ in vitro antibacterial activity was demonstrated and catechins present in the extracts are, most likely, the bioactive compounds responsible for this action.